Research on the Influence of Fault Arc on Polyimide Insulation Materials. Issue 1 (1st January 2023) - Tang, Muhan; Yue, Pengcheng; Duan, Xiongying; Ma, Chang; Kong, Fancong; Liao, Minfu
Abstract: In modern grid systems, electrical fires caused by faulty arcs occur more frequently. Arc protective clothing is the equipment that can effectively protect personal safety. Among them, polyimide insulation materials have the advantages of high-temperature resistance and high thermal resistance. Their performance in the field of arc protection is of high research value. In this paper, the effect of faulty arc on polyimide insulation material is studied by experimental and simulation control modes. The COMSOL software is used to simulate the process of electric arc affecting polyimide insulation material, and to simulate the physical field distribution of electric arc with different electrode spacing and different arc currents. An arc generation device is built, a copper calorimeter is designed to record the temperature rise of each experiment, a variety of arc parameters is changed, and the performance of polyimide insulation materials is analyzed to block the fault arc. A fault arc experimental platform was built, using a copper calorimeter to record the temperature rise of each experiment. Varying multiple arc parameters to analyze the performance of polyimide insulation materials in blocking fault arcs. The simulation and test results show that polyimide has an obvious barrier effect on the radiation temperature of the fault arc, and it can show good thermal insulation under different arc conditions, which proves that polyimide insulation materials have excellent protection performance against fault arcs in the energized operation environment.